Reduced neonatal regulatory T cell response to microbial stimuli associates with subsequent eczema in high risk infants - Ismail, Intan Hakimah; Boyle, Robert J.; Li, Jeen Mah; Licciardi, Paul V.; Tang, Mimi L. K. (Wiley, 2015)
Background: Regulatory T cells (Treg) play an essential role in early immune programming and shaping the immune response towards a pro‐allergic or tolerant state. We evaluated cord blood Treg and cytokine responses to microbial and non‐microbial stimuli in infants at high risk of allergic disease and their associations with development of allergic disease in the first year.